2010
DOI: 10.5897/ajb09.1278
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of cryptosporidium infection in children under five years of age having diarrhea in the North West of Pakistan

Abstract: Cryptosporidium species are minute, coccidian protozoan parasites that have been associated with enterocolitis. It has worldwide distribution and has emerged as an important cause of diarrhea, particularly in children less than 5 years of age and in immunocompromised individuals. Waterborne transmission is particularly troublesome because Cryptosporidium parvum oocysts are not eliminated by chlorination or domestic disinfectants. In the present study, single stool specimens from young children (< 5 years) pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Poor health practices, illiteracy, limitation in drinking water supply, lack of sewage, and its management for drainage of human and animal waste disposals can substantiate the occurrences of this infection in the vulnerable populations of developing countries. The prevalence of Cryptosporidiosis is higher in developing countries 5.9-17%, compared to developed countries 0.1-2% 9 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Poor health practices, illiteracy, limitation in drinking water supply, lack of sewage, and its management for drainage of human and animal waste disposals can substantiate the occurrences of this infection in the vulnerable populations of developing countries. The prevalence of Cryptosporidiosis is higher in developing countries 5.9-17%, compared to developed countries 0.1-2% 9 .…”
Section: Introductionmentioning
confidence: 91%
“…The previous reports from different parts of Ethiopia particularly in eastern, central, and northwest Ethiopia indicated the importance of the disease in cattle and estimated the prevalence range from 2.3% to 27.8% in calves as a result of immature immunity, poor farm management, and hygienic condition 18,19 . Moreover, different studies indicated the significance of the disease in children due to immature immunity, contamination of drinking water, poor personal hygiene, and contact with domestic animals, especially with calves 9,20 . The prevalence of Cryptosporidiosis ranges between 3.3% and 14.8% in underfive years children in different countries 21,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this contaminated canal water is used for irrigation purpose by which our vegetables and fodders got contaminated. Humans and animals got infected when they eat them in raw form (Mumtaz et al 2010;Alam et al 2014). Among these protozoa, most pathogenic are Cryptosporidium spp., Giardia spp., and Entamoeba spp.…”
Section: Water-borne Git Protozoamentioning
confidence: 99%
“…Water borne protozoan infection is a global issue and is reported from a number of countries including Australia (Ma et al 2022), Africa (Abuseir 2023), Bangladesh (Alam et al 2014), Brazil (Taverne 2002), Bulgeria (Sotiriadou and Karanis 2008), Canada (Herwaldt 2000;Wallis et al 2001;Ho et al 2002;Murrow et al 2002;Hopkins et al 2013), China (Zhang et al 2011;Lv et al 2013;Liu et al 2014), Ethiopia (Ayalew et al 2011), France (Dalle et al 2003;Villena et al 2004;Aubert and Villena 2009), Germany (Gornik et al 2000;Gallas-Lindemann et al 2013), Iraq (Raza and Sami 2009), Iran (Mahmoudi et al 2015), Ireland (Glaberman et al 2002;Jennings and Rhatigan 2002), India (Kiran et al 2014;Jain and Nahri 2015), Japan (Uga et al 2005;Kourenti and Karanis 2006), Korea (Cheun et al 2013;Moon et al 2013), Malaysia (Mahsol et al 2008;Kumar et al 2014), Nepal (Sah et al 2013), Netherland (Schets et al 2008), New Zealand (Webber 2002), Pakistan (Ahsan-ul-Wadood et al 2005Mumtaz et al 2010;Chaudhary and Chandra 2012;Khan et al 2013;Masood et al 2013;…”
Section: Global Distribution Of Water-borne Protozoamentioning
confidence: 99%
See 1 more Smart Citation